The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1103/physrevb.71.174111
|View full text |Cite
|
Sign up to set email alerts
|

Rare-gas solids under pressure: A path-integral Monte Carlo simulation

Abstract: Rare-gas solids (Ne, Ar, Kr, and Xe) under hydrostatic pressure up to 30 kbar have been studied by path-integral Monte Carlo simulations in the isothermal-isobaric ensemble. Results of these simulations have been compared with available experimental data and with those obtained from a quasiharmonic approximation (QHA). This comparison allows us to quantify the overall anharmonicity of the lattice vibrations and its influence on several structural and thermodynamic properties of rare-gas solids. The vibrational… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
(92 reference statements)
4
16
0
Order By: Relevance
“…For example, at T = 20 K and P = 1 GPa, we find for solid 4 He: B = 4.53 GPa, vs 7.20 and 9.43 for Ne and Ar, respectively [30]. This is in line with the known result that the bulk modulus increases with atomic mass for given values of temperature and pressure [30].…”
Section: B Pressure and Temperature Dependencesupporting
confidence: 89%
“…For example, at T = 20 K and P = 1 GPa, we find for solid 4 He: B = 4.53 GPa, vs 7.20 and 9.43 for Ne and Ar, respectively [30]. This is in line with the known result that the bulk modulus increases with atomic mass for given values of temperature and pressure [30].…”
Section: B Pressure and Temperature Dependencesupporting
confidence: 89%
“…Their result for A is in good agreement with the present value (A = 2.88 at 0.53 GPa). With respect to the C 11 , C 12 , and C 44 , we cannot directly compare the elastic properties under low temperature [6,13] with the present ones, because the elastic constants for rare-gas solids strongly depend on the pressure and temperature.…”
Section: Resultsmentioning
confidence: 99%
“…(67)], which dominates at high pressures. Results of these PIMC simulations indicated that the accuracy of the QHA to describe noble-gas solids increases as pressure is raised 115 . This is mainly a consequence of the relative importance of elastic and vibrational energy, as the latter becomes comparatively irrelevant as pressure rises.…”
Section: B Heavier Elementsmentioning
confidence: 99%
“…For rising Λ, these effective potentials become increasingly softer, shallower, and of longer range, with the potential minimum shifted to larger distances. Given the importance of anharmonic effects in noblegas solids, PIMC simulations have been employed to assess the accuracy of harmonic or quasi-harmonic approximations for vibrational modes in these solids under pressure 115 . This allowed to quantify the overall anharmonicity of the lattice vibrations and its influence on several structural and thermodynamic properties.…”
Section: B Heavier Elementsmentioning
confidence: 99%